God's word to Israel - Jensen, Joseph (Liturgical Press, 2021)
Intro -- Title Page -- Copyright -- Contents -- Foreword -- Preface -- References and Abbreviations -- 1 Word of God and People of God -- Suggestions for Further Reading -- 2 Modern Study of the Bible -- Literary Criticism -- Biblical Archaeology -- Literary Finds -- Dead Sea Scrolls-Textual Criticism -- Ecumenism -- Suggestions for Further Reading -- 3 Panorama -- Suggestions for Further Reading -- Brief Chronological Chart -- 4 The Composition of the Pentateuch -- The "Classical Theory" of Documents -- The Contribution of Wellhausen -- After Wellhausen -- The Individual Source-Traditions -- Source-Tradition J -- Source-Tradition E -- Source-Tradition D -- Source-Tradition P -- Later Advances in Pentateuchal Studies -- Suggestions for Further Reading -- 5 Primeval History -- Sources, Literary Form, and Historicity -- Creation and Fall -- First Creation Account: Gen 1:1-2:4a (P) -- Second Creation Account and the Fall: Gen 2:4b-3:24 (J) -- From the Fall to Abraham -- Cain and Abel: Gen 4:1-6 (J) -- Genealogy: Genesis 5 (P) -- The Flood: Gen 6:1-9:17 (J and P) -- The Tower of Babel: Gen 11:1-9 (J) -- Suggestions for Further Reading -- Appendix on "Evolution," "Creationism," and "Intelligent Design" -- 6 A Wandering Aramaean -- Summons and Promise -- Sources and Historicity -- Religious Significance of Patriarchs -- Suggestions for Further Reading -- 7 "Out of Egypt I Called My Son" -- Land of Bondage -- Deliverance from Egypt -- Sojourn, Exodus, and History -- Call of Moses -- Signs and Wonders -- Events at Sinai -- Covenant -- Construction of the Tabernacle (Dwelling) -- Law -- Wilderness Generation -- Suggestions for Further Reading -- 8 Deuteronomy and the Deuteronomic School -- The Origin of Deuteronomy -- The Spirit of Deuteronomy -- YHWH Alone -- Unity of Sanctuary -- Rewards and Punishments -- Choose Life Today!.